2018
DOI: 10.1007/s11657-018-0431-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric semi-quantitative assessment of vertebral fractures in postmenopausal black women in Central Africa

Abstract: This study seemed to determine the pattern and features of vertebral fractures in black African women which may be useful for comparisons with the pattern of worldwide populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…26 However, the prevalence is higher than that seen in the Democratic Republic of Congo (DRC), Cape Town and in The Gambia. [9][10][11] This may be explained by the inclusion of younger and/or premenopausal women in The Gambia and Cape Town or the lower mean age of the postmenopausal female subjects in the DRC, which was 15 years lower than that in the current study.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…26 However, the prevalence is higher than that seen in the Democratic Republic of Congo (DRC), Cape Town and in The Gambia. [9][10][11] This may be explained by the inclusion of younger and/or premenopausal women in The Gambia and Cape Town or the lower mean age of the postmenopausal female subjects in the DRC, which was 15 years lower than that in the current study.…”
Section: Discussioncontrasting
confidence: 62%
“…5,6 A similar prevalence (16.2%) has also been reported in Tunisian postmenopausal women, while a higher prevalence (25.6%) was reported in Moroccan women. 7,8 In contrast, a lower prevalence of morphometric VFs was seen in postmenopausal black women in a multi-centre study from Central Africa (11%) 9 and in Gambian women (6%). 10 These differences may be due to methodological or ethnic differences.…”
Section: Introductionmentioning
confidence: 93%
“…85 In a cohort of 430 postmenopausal women living in Kinshasa, Democratic Republic of Congo, who complained of back pain, vertebral fractures were diagnosed in 11% of the thoraco-lumbar vertebrae; the prevalence of fractures rose with age. 86 In the Gambia, a cross-sectional study of 488 healthy men and women >40 years of age from Kiang West were found to have a prevalence of 9% moderate or severe vertebral fractures on DXA. 62 Regional considerations summary.…”
Section: Regional Considerations High-income Countriesmentioning
confidence: 99%
“…The majority of studies have been focusing on the experience and reported symptoms during menopausal transition and menopause [ 11 - 15 ]. Studying menopause and menopause-associated disorders such as osteoporosis, metabolic syndrome, and prehypertension have been the subject of interest for researchers in the Democratic Republic of the Congo (DRC) [ 16 - 19 ]. However, none of them have considered assessing the awareness of the definition, the symptoms, the attitudes, and the practices towards menopause among middle-aged and/or postmenopausal Congolese women.…”
Section: Introductionmentioning
confidence: 99%